EFEKTIVITAS PENGGUNAAN APLIKASI DIGITAL AL-QUR’AN (NU ONLINE) TERHADAP PENINGKATAN KEMAMPUAN TILAWAH SISWA SMP ISLAM AN-NADWAH - Afiatna, Fajar; Fauziyah, Nur Laily; Hidayatulloh, M Agung (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
This study aims to determine the implementation of the NU Online digital Qur'an and analyze the level of recitation ability of grade VII students, before and after using the digital Qur'an. The research method used was quantitative research with a pretest-posttest design. The sample consisted of 50 seventh-grade students of An-Nadwah Islamic Middle School, selected purposively. The research instrument was an oral recitation test that assessed four aspects of the ability to read the Quran, namely accuracy of the pronunciation of the letters, application of tajweed, fluency, and accuracy of the rhythm of the reading. Data were analyzed using normality test, linearity test, Pearson correlation, and paired sample t-test to determine significant changes before and after treatment. The average pretest score of 74.88 increased to 79.10 in the posttest. The normality test yielded significance values of 0.486 (pretest) and 0.474 (posttest), indicating a normally distributed data. The paired sample t-test yielded a significance value of 0.000 0.05 with a t-value of -21.709, indicating a significant difference between recitation ability before and after treatment. The correlation coefficient of 0.995 indicates a very strong relationship between application utilization and the improvement of students' recitation ability.